2013
DOI: 10.1128/jvi.02147-12
|View full text |Cite
|
Sign up to set email alerts
|

The Cellular Autophagy Pathway Modulates Human T-Cell Leukemia Virus Type 1 Replication

Abstract: Autophagy, a general homeostatic process for degradation of cytosolic proteins or organelles, has been reported to modulate the replication of many viruses. The role of autophagy in human T-cell leukemia virus type 1 (HTLV-1) replication has, however, been uncharacterized. Here, we report that HTLV-1 infection increases the accumulation of autophagosomes and that this accumulation increases HTLV-1 production. We found that the HTLV-1 Tax protein increases cellular autophagosome accumulation by acting to block … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 82 publications
3
57
0
Order By: Relevance
“…Tang et al reported that HTLV-1 Tax increased autophagy could enhance HTLV-1 replication and production by preventing the degradation of Tax (41). Another report showed that HTLV-2 Tax-mediated autophagy promoted survival and proliferation of immortalized T cells (42).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tang et al reported that HTLV-1 Tax increased autophagy could enhance HTLV-1 replication and production by preventing the degradation of Tax (41). Another report showed that HTLV-2 Tax-mediated autophagy promoted survival and proliferation of immortalized T cells (42).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the regulation by Tax of the autophagy pathway was also reported (41,42). However, the relationship between Tax-regulated apoptosis and autophagy is still unclear.…”
Section: Htlv-1 Tax Increases Autophagosomes Accumulationmentioning
confidence: 99%
See 1 more Smart Citation
“…This also seems to be the case for another retroviral transactivator, the human T-cell leukemia virus type 1 (HTLV-1) Tax protein. Indeed, it has been demonstrated that Tax is a substrate for autophagy degradation, but the underlying mechanism is still unknown (51). They also demonstrated that Tax is able to block the degradative phases of autophagy, suggesting that this viral protein could control its own stability and turnover (51).…”
Section: Discussionmentioning
confidence: 99%
“…Several HTLV-1 chronically infected T-cell lines are available for in vitro studies and have been used to infect T lymphocytes (17,20,21). However, DC infection was performed using MT-2 cells only (10,22), while HTLV-1 transcytosis experiments were done using C91PL cells only (19).…”
Section: C91pl Cells Produce More Infectious Viral Particles Than Mt-mentioning
confidence: 99%